GIS-based noise spatial distribution map using mobile / Syaza Rozali and Siti Aekbal Salleh - Rozali, Syaza; Salleh, Siti Aekbal (Faculty of Architecture, Planning and Surveying, 2016)
Noisetube apps are used as a platform to collect noise data. However, the data from crowdsourcing are shown as points of locations that is difficult for interpretation. Therefore, to visualize better presentation of noise maps, interpolation method from GIS software tools is used for data processing and analysis. The aim of this study is to prepare noise pollution distribution using mobile apps in UiTM Shah Alam. Based on the aim, the objective is to measure and record sound level data by apps and investigate suitable interpolation methods for creating a continuous surface from discrete points for noise analysis. With the global positioning system (GPS) provided in a smartphone and internet data, NoiseTube apps will run their system for measuring noise data with location. The data will be sent, stored and processed in NoiseTube server so that it can be downloaded and viewed by the user. An accuracy of data is considered by performing calibration process. ArcGIS desktop software is used to perform data processing and analysis by testing difference interpolation method such as Kriging, CoKriging and Inverse Distance Weighting (IDW). Analysis is carried out to identify the crowded place in Education zone. The result shows that ordinary CoKriging is the suitable interpolation method for mapping the noise distribution based on data collected in this study area. The calibration result shows that smartphone is less accurate for noise measuring based on the calibration test result about 7 decibel unit compared to the actual reading from the sound level meter instrument.